A Challenge to Three Widely Held Ideas in Environmental Valuation. (August 2014) - Interis, Matthew G.
Abstract : Environmental valuation is the branch of environmental economics in which researchers estimate the economic value of environmental goods and services. Environmental valuation has been practiced for decades. However, there are some ideas in the field of environmental valuation held by many environmental economists and nonenvironmental economists that appear to be outdated. This article discusses three such ideas: 1) that it is better to estimate willingness-to-pay values than willingness-to-accept values; 2) that stated preference valuation methods are questionable because they are based on hypothetical choices rather than real choices; and 3) that it is better to use a repeated-choice question format than a single-choice format in choiceexperiments. We discuss the origins of each idea and why the idea became prevalent in the first place. We then review recent literature, which casts doubt on the idea. We conclude with a reminder for researchers—in environmental economics and in other economic fields—to periodically reassess ideas they currently hold in light of recent research developments and in light of the context in which they are used.